Cracking reasons and features of fatigue details in the diaphragm of curved steel box girder. (15th December 2019) - Wang, Yixun; Fu, Zhongqiu; Ge, Hanbin; Ji, Bohai; Hayakawa, Norihiko
Highlights: The cracking reasons were studied considering influence of the curvature. The cracking features were investigated and verified by the fatigue experiment. The fatigue tests were carried out by eccentric loadings to simulate the wheels. Effects of interference on fatigue cracks in the diaphragm were studied. Abstract: The cracking reasons and features of fatigue details in the diaphragm of curved steel box girder were studied based on a real curved steel bridge with three spans located in Nagoya, Japan. The cracking conditions of certain fatigue details were summarized according to in situ monitoring data. The in-plane and out-of-plane deformation was analyzed considering structural features and loading conditions of the bridge as a whole. The influence of the curve on fatigue characteristics was investigated and reasons for cracking were concluded. Moreover, the fatigue test was carried out on cracking details to verify cracking behaviours in the real bridge, based on which the cracking laws were summarized. The results indicated that the unevenly distributed loadings caused by the curvature resulted in a greater stress on outside details than on inside details in the curved steel box girder, which was the major difference in the fatigue characteristics between curved and straight steel box girders. The eccentricity of vehicle loadings and structural characteristics were the major reasons behind the antisymmetric propagation of the cracks in the diaphragm-web rib weld. Apparent interference could be observed in the fatigue cracks of the diaphragm-U rib weld on both sides of an identical U rib.